Translation, Cross-cultural Adaptation and Validation of the Neck Bournemouth Questionnaire: Persian Version - Mohammad Mehdi Salaree (Tabriz University of Medical Sciences, 2021)
Introduction: The Neck Bournemouth Questionnaire (NBQ) is being used widely in various countries. This study evaluated the validity and reliability of the Persian version of NBQ. Methods: This methodological study investigated 170 patients with chronic neck pain (NP). The psychometric properties of NBQ were evaluated in two stages. First, the standard scale was translated based on Guillemin’s guidelines for cross-cultural adaption and face validity tested in a pilot group (N=25). Second, it was conducted on a sample of 170 diverse chronic pain patients. Construct validity was determined with convergent validity by short-form McGill pain questionnaire. Then, the reliability was confirmed using Cronbach’s alpha and the intraclass correlation coefficient. Results: The instrument demonstrated a good face validity and the participants made minor changes. A slight change was applied on content validity. In construct validity, Pearson’s correlation coefficient was 0.85, which was statistically significant and showed strong correlation. A Cronbach’s alpha of 0.87 was obtained. This confirmed the remarkable internal consistency and stability (0.92). Conclusion: The Persian version of NBQ showed a good internal consistency and reliability and it could be considered as a valuable tool for assessing patients with cervical pain in Iranian population.